Effect of Leadership Styles on Employees’ Innovative Behaviour: The Mediating Role of Employees’ Creativity: The Impact of Comprehensive Leadership on Employees' Innovative Behavior: A Study in Chinese Organizations (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In spite of broad writing on administration and its effect employee innovative behavior, few examinations have investigated the connection between comprehensive initiative and employee innovative behavior. To address this hole, this examination intended to research how comprehensive administration impacted employee innovative behavior by looking at apparent hierarchical help (POS) as an arbiter. We utilized multi-wave and multi-source information gathered at 15 organizations in China to test our hypothetical model. Results uncovered that comprehensive authority had essentially beneficial outcomes on POS and employee innovative behavior. Moreover, POS was emphatically identified with employee innovative behavior and mostly intervened the connection between comprehensive initiative and employee innovative behavior. We talked about suggestions and confinements of this examination just as roads for future research.